PERAN FOOD AND AGRICULTURE ORGANISATION (FAO) DALAM MENANGGULANGI MASALAH KELAPARAN DI INDIA PADA TAHUN 2011-2014 - Ivan Kurniawan; Faisyal Rani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
This research is trying to explain about Food and Agriculture Organisation role in India in trying to reduce the hungry population that exist in the country. FAO is an organisation that works on food and agriculture sector and one of many organisation under the wings of United Nations have the obligation to help India resolve the issues whereas India is one of UN and FAO member or as a human right obligations. This research is using Pluralism Perspective, pluralism is a perspective that put forward the necessity of non-state actor in international relations, this perspektif also set the human right issues as high regard that need to be resolved together. This research also use international organisation theory which explain the role of FAO in India itself. Hunger is a major issues of India since their independence. Hunger in India itself is affected by natural issues such as natural disaster, climate change, and drought. The issues also influenced by social aspect such as overpopulation, lack of knowledge in natural issues, and poverty. FAO enter India as an organization that try to facilitate and resolve this issues, whereas FAO try to build an infrastructure that satisfy the internasional standard and trying to give the knowledge to Indian farmer and agricultural investor to change their view on agricultural field and understanding the optimal ways in processing the harvested goods that can be marketed internationally.Keywords: Hunger in India, FAO, Facilitator